2021
DOI: 10.3390/jcm10194494
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Preterm Baby Arrival in a Family: A Descriptive Cross-Sectional Pilot Study

Abstract: Background: The rate of premature births is increasing every day, with an estimated 15 million premature babies born worldwide each year. When a child is born prematurely, he or she is transferred to a Neonatal Intensive Care Unit (NICU), requiring special care on an ongoing basis. The admission of the newborn to these units can negatively affect the family routine as it generates changes and requires adaptation to new roles. Objectives: The objective of the present study was to understand the effect of the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…The literature has recognized the effects of interventions of humanization on affective perception in several hospital wards, such as Psychiatry, Radiology, Stem Cell Transplant Centre, and Pediatrics [ 42 , 52 , 54 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Nevertheless, no attention has been paid to the NICUs, often described by parents as unfamiliar, disturbing, and highly distressing environments [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature has recognized the effects of interventions of humanization on affective perception in several hospital wards, such as Psychiatry, Radiology, Stem Cell Transplant Centre, and Pediatrics [ 42 , 52 , 54 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Nevertheless, no attention has been paid to the NICUs, often described by parents as unfamiliar, disturbing, and highly distressing environments [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we found, in particular, that the scores for all negative subscales of QAL (distressing, unpleasant, gloomy and sleepy) were significantly lower after the implementation of intervention. This result has clinical implications, suggesting that this intervention may reduce the sense of unfamiliarity and discomfort reported by parents during their stay in the NICU [ 10 , 11 , 12 ]. This explanation is further supported by the fact that parents, after the pictorial humanization, obtained higher scores at three of the positive QAL subscales: pleasant, exciting, and arousing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El ingreso del recién nacido a hospitalización puede afectar negativamente la vida familiar, ya que genera cambios y requiere adaptación a nuevos roles (Jiménez et al 2021), por esta razón, el presente trabajo investigativo tiene como objetivo principal evaluar el estado de salud mental en las madres de recién nacidos ingresados en el servicio de neonatología.…”
Section: Introductionunclassified
“…Studies explored concepts, such as parental occupational balance in parents of babies born at a very low birth weight who were admitted to a NICU, 22 the experiences of fathers with inpatient premature neonates who experienced occupational disruption, 23 and a cross-sectional study on occupational imbalances in parents following the birth of a baby born preterm and admitted to a NICU. 24 A preliminary search of PROSPERO, MEDLINE, the Cochrane Database of Systematic Reviews, and JBI Evidence Synthesis was conducted and no current or in-progress scoping reviews or systematic reviews on the topic were identified. The rationale for a scoping review on this topic is clear given the potential for occupational justice concepts to enhance clinical OT practice.…”
Section: Introductionmentioning
confidence: 99%